Abplatin(IV) inhibited tumor growth on a patient derived cancer model of hepatocellular carcinoma and its comparative multi-omics study with cisplatin - Xing Li; Lingpu Zhang; Tuo Li; Shumu Li; Wenjing Wu; Lingyu Zhao; Peng Xie; Jinqi Yang; Peipei Li; Yangyang Zhang; Haihua Xiao; Yingjie Yu; et al. (Journal of Nanobiotechnology, 2022)
Abstract Background Cisplatin, the alkylating agent of platinum(II) (Pt(II)), is the most common antitumor drug in clinic; however, it has many side effects, therefore it is higly desired to develop low toxicity platinum(IV) (Pt(IV)) drugs. Multi-omics analysis, as a powerful tool, has been frequently employed for the mechanism study of a certain therapy at the molecular level, which might be helpful for elucidating the mechanism of platinum drugs and facilitating their clinical application. Methods Strating form cisplatin, a hydrophobic Pt(IV) prodrug (CisPt(IV)) with two hydrophobic aliphatic chains was synthesized, and further encapsulated with a drug carrier, human serum albumin (HSA), to form nanoparticles, namely AbPlatin(IV). The anticancer effect of AbPlatin(IV) was investigated in vitro and in vivo. Moreover, transcriptomics, metabolomics and lipidomics were performed to explore the mechanism of AbPlatin(IV). Results Compared with cisplatin, Abplatin(IV) exhibited better tumor-targeting effect and greater tumor inhibition rate. Lipidomics study showed that Abplatin(IV) might induce the changes of BEL-7404 cell membrane, and cause the disorder of glycerophospholipids and sphingolipids. In addition, transcriptomics and metabolomics study showed that Abplatin(IV) significantly disturbed the purine metabolism pathway. Conclusions This research highlighted the development of Abplatin(IV) and the use of multi-omics for the mechanism elucidation of prodrug, which is the key to the clinical translation of prodrug. Graphical Abstract